A stable MOF@COF‐Pd catalyst for C–C coupling reaction of pyrimidine sulfonate and arylboronic acid. (13th June 2022) - Yang, Quanlu; Zhang, Ying; Ding, Ning; Hu, Qiang; Yan, Xiangtao; Liu, Jutao; Zhang, Penghui; Fu, Shuaishuai; Wang, Qianshan; Wu, Lan; Wu, Shang
Abstract: A novel type of porous composites MOF@COF was successfully constructed through decorating covalent organic framework (COF) crystals on the surface of amino‐functionalized metal organic framework (NH2 ‐MOF). This material has proven to be an excellent catalyst support because it not only overcomes the shortcoming of MOF instability but also combines the advantages of both high specific surface areas. Pd (OAc)2 is anchored on MOF@COF to obtain MOF@COF‐Pd catalyst. MOF@COF‐Pd is used to catalyze the C–C coupling reaction of pyrimidine sulfonate and aryl boronic acid. The catalyst has the advantages of high stability, catalytic activity, recyclability, and no metal loss. And the application of MOF@COF hybrid materials was expanded in the field of catalysis. Abstract : MOF@COF hybrid material carrier has a higher specific surface area. MOF@COF‐Pd catalyst can catalyze the C–C coupling reaction stably and efficiently. MOF@COF‐Pd can be recycled five times while the catalytic activity is only reduced by 8%.